Produção de leite no Rio Grande do Sul: a distribuição espacial e a relação de dependência entre os municípios - Schumacher, Gabriela (2013)
The study analyzes the spatial distribution of milk production in the municipalities and the relation of dependence between them in Rio Grande do Sul in 2010. The research is characterized as quantitative and ex post facto, and the statistical method used in the analysis. The data collection was made from the data query side of 496 municipalities of the State of Rio Grande do Sul for the year 2010. Initially, we calculated the location quotient to identify the municipalities and specialized after we used spatial econometric techniques to identify whether there are spillover between them. The results show that in 2010 the Rio Grande do Sul 128 municipalities had specialized in the production of milk, the top ten are located in the regions of the Northwest, Northeast and Mid-East. The same result was found by exploratory spatial data analysis (ESDA), which highlighted how important these poles milk production. The Moran's I statistic indicated that there is a positive spatial autocorrelation for the gross value of milk production, suggesting the existence of spatial dependence. The econometric tests have confirmed from the spatial lag model that overflow exists between municipalities. This effect was best explained by variable capital, labor, pasture area, electricity, education, average rainfall, paved and unpaved roads.